BS EN 2267-012. Aerospace series. Cables, electrical, for general purpose. Operating temperatures between -55 °C and 260 °C. Part 012. DZ family, single UV laser printable for use in low pressure atmosphere. Product standard (16th June 2022) - British Standards Institution,
No abstract available